2017
DOI: 10.26532/sainsmed.v8i1.1050
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Green Tea Leaf Extract on Spatial Memory Function and Superoxyde Dismutase Enzyme Activity in Mice with D-galactose Induced Dimentia

Abstract: Background:�Oxidative stress�and�inflammation�play�an important role in�pathogenesis of�brain aging�and neurodegenerative diseases such as�Alzheimer. Green tea�has been shown to have antioxidant, anti-inflammatory, anticancer, and neuroprotective�activity. Objectives: to determine the effect of green tea extract on�spatial memory function and superoxide dismutase�enzyme activity in mice with D-galactose induced dementiaMethods:�An experimental study using "post test only control group design".�Twenty m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…D-galactose (150 mg/kgbw) injected subcutaneously for 6 weeks, caused the effects of aging, cognitive impairment and neurodegenerative diseases such as dementia. 25,31 The study showed brain aging with D-galactose induced at dose 100 mg/kgbw for 8 weeks. The accelerated induced aging model might be promising tool for human brain aging model in mice.…”
Section: Immunoexpression Of P16ink4a In the Induced Aging Modelmentioning
confidence: 99%
“…D-galactose (150 mg/kgbw) injected subcutaneously for 6 weeks, caused the effects of aging, cognitive impairment and neurodegenerative diseases such as dementia. 25,31 The study showed brain aging with D-galactose induced at dose 100 mg/kgbw for 8 weeks. The accelerated induced aging model might be promising tool for human brain aging model in mice.…”
Section: Immunoexpression Of P16ink4a In the Induced Aging Modelmentioning
confidence: 99%